Pendampingan Guru Sekolah Dasar Dalam Meningkatkan Kreativitas Belajar Peserta Didik Melalui Pendekatan Pembelajaran Kontekstual - Ahmad, Marzuki (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The learning activities that occur tend to be dominated by student activities such as paying attention, looking at the teacher's explanation of the material and examples, and discussing practice questions according to the examples. This makes learning creativity less fun. Learning that is carried out should involve students being active both in finding concepts and learning materials, solving problems, and comparing and discussing concepts/ and aterials and the results of problem solving.hus, it is necessary to apply learning that pays attention to the development of learning creativity, one of which is the contextual learning approach. The purpose of this activity is to increase student creativity through a contextual learning approach. Community service activities are carried out using the Participatory Action Research (PAR) method, which involves socialization, implementation and monitoring, and program evaluation activities. Data collected from questionnaires and interviews. The community service activities carried out show the conclusion that student creativity increases through contextual learning and is an effective criteria. Furthermore, each indicator of learning creativity increases based on the application of contextual learning components; namely, components in contextual learning have a dominant influence on learning creativity indicators.